1985
DOI: 10.1161/01.cir.72.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 15-HETE synthesis by human umbilical vein endothelial cells.

Abstract: Incubation of cultured human umbilical vein endothelial cells with -4C]-arachidonic acid, followed by RP-HPLC analysis, resulted in the appearance of two principal radioactive products besides 6-keto-PGF,. The first peak was HHT, a hydrolysis product of the prostaglandin endoperoxide. The second peak was esterified, converted to the trimethylsilyl ether derivative, and analyzed by GC/MS and was shown to be the lipoxygenase product 1 5-HETE. Stimulation of endothelial cells with thrombin enhanced 15-HETE synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…The data shown in Fig. 4 and Tables I and II demonstrate that porcine endothelial cells produce both 5-and 15-HETE, as has been previously indicated for human umbilical endothelial cells (5,6). The decreased net release of arachidonic acid was evident after 5 min and was striking after 30 min.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The data shown in Fig. 4 and Tables I and II demonstrate that porcine endothelial cells produce both 5-and 15-HETE, as has been previously indicated for human umbilical endothelial cells (5,6). The decreased net release of arachidonic acid was evident after 5 min and was striking after 30 min.…”
Section: Discussionsupporting
confidence: 84%
“…Both elevated platelet TXA2 and diminished vascular prostacyclin (PGI2) synthesis have been reported (1,2). In addition to cyclooxygenase-derived products, both platelets and endothelial cells produce hydroxyeicosatetraenoic acids (HETEs),1 metabolized by the lipoxygenase pathway of arachidonic acid oxygenation (3)(4)(5)(6)(7). Several studies have suggested that these HETEs may influence the production of PGI2 (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, whether or not a constitutive production of LTA 4 and the other leucotrienes occur in these cells is controversial at present. In aortic and other arterial EC from various animals, 5-, 12-, 15-HETE and LTB 4 have been identified, demonstrating a constitutive expression of 5-, 12-and 15-LOX activity in EC at these locations [14,15,37,38]. However, the presence of 5-LOX in HUVEC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lymphocytes, erythrocytes represent another example of cells virtually devoid of dioxygenase activity (Schrier, 1967;Kobayashi & Levine, 1983), which are however able to generate lipid mediators through cell-cell interactions. Further metabolism of LTA4 into peptidoleukotriene, LTC4 [(5S) -hydroxy -(6R) -S-glutathionyl -7,9,11,14eicosatetraenoic acid], by vascular endothelium, which is unable to produce LTA4 itself (Gorman et al, 1985;Miller et al, 1985), has been described (Feinmark & Cannon, 1986). Similar conversion has been observed in platelets, which also fail to synthesize LTA4 (Maclouf & Murphy, 1988).…”
Section: Oxygenated Eicosanoids As Biochemical Precursorsmentioning
confidence: 99%